Two-canal System in Primary Maxillary Central Incisors: A Rare Case Report - KV Lakshika Sree; Daya Srinivasan; Abishek C Balasubramanian; Subakeerthi Thangavel (Journal of South Asian Association of Pediatric Dentistry)
Aims and background: Root canal variations in primary maxillary central incisors are uncommon and influence the success of endodontic treatment if not properly diagnosed. This case aims to discuss a rare presentation of a primary maxillary central incisor with two distinct root canals. Case description: A 4-year-old male child reported with pain in the upper front teeth region. Clinical evaluation, including radiographic imaging and electric pulp testing, indicated symptomatic irreversible pulpitis. Cone-beam computed tomography (CBCT) confirmed the presence of two separate root canals. A pulpectomy was carried out, followed by the placement of a zirconia crown, with follow-up assessments at 6 months showing favorable outcomes. Conclusion: Accurate diagnosis, supported by radiographic evaluation, was pivotal in managing this case with an unusual canal configuration for the treatment success. Clinical significance: Radiographic tools, including CBCT, play a key role in accurate diagnosis and successful pediatric endodontic treatment.